ANALISIS PENAMBAHAN JUMLAH WATER TRAP UNTUK MENGATASI TERJADINYA PENYUMBATAN JALUR SEMEN PADA SAMPLER FM1 DI PT. SOLUSI BANGUN INDONESIA-TUBAN - Bayu Bakti Pradana; Suhariyanto (Universitas Muhammadiyah Surabaya, 2025)
Abstract Sampler Finish Mill 1 (Sampler FM1) is equipment that used to collect sample in cement production process in PT. Solusi Bangun Indonesia. During running time, Sampler FM1 usually got blocking in the material line about 8 times during 2023. When got blocking, the quality value of sample cement from Sampler FM1 can be different than sample from sample cement from Bucker Elevator (BE) that used to be reference value. This problem caused by the air that enter to the system in Sampler FM1 have high relative humidity value because Water Trap that installed in Sampel FM1 allegedly lacking. So, it needs observation and analysis condition of material line dan air at Sampler FM1 and the impact to the quality of cement at before and after installation new Water Trap at Sampler FM1. Depend on background problem that appear, so it needs observation and analysis about condition of material line dan air at Sampler FM1 and analysis comparison of cement quality between Sampler FM 1 and BE. When founded material line blocking, high relative humidity and deviation of cement quality, so it needs to install Water Trap again to solve this problem. Designed and installation new Water Trap by Maintenance Laboratory Team. After installation of new Water Trap, it needs to observation and analysis again about the condition of material line and air at Sampler FM1 and analysis about quality comparation between sample cement from Sampler FM1 and BE. Depend from observation, calculation and analysis additional amount of Water Trap at Sampler FM1, it can be concluding as follow: before installed additional Water Trap, condition of Sample FM1 often got blocking caused by air that entered to Sampler FM1 was too humid, this problem can be proved the value of relative humidity air at Sampler FM1 reached 88% and H2O value of cement sample more than 0.5%. When Sampler FM1 got blocking, quality of cement sample form Sample FM1 and Bucket Elevator is different during transition time of process production cement. This problem can be proving the value of SO3 contain, Blaine, Residue R45µm, and H2O is different. After installed a new Water Trap, condition of Sampler FM1 is unblocking after 2 weeks operational time because the air that entered in to Sampler FM1 become dry, it proves by Relative Humidity value of air at Sampler FM1 become 43% and H2O contains of cement sample from Sampler FM1 become less than 0.5%. After installation a new Water Trap, the condition of material way of Sampler FM1 become unblocking, so the quality cement between Sampler FM1 and BE become similar during transition time of process production cement. It proves by SO3 contain, Blaine and Residue R45µm is similar, but H2O contain of cement from Sampler FM1 is still higher than Bucket Elevator. Key words: Sampler FM1, Water Trap, Cement Quality.